Prevalence of post major burn complications, posttraumatic stress disorder and depression among HUSM patients treated for major burn between 2006 and 2016 - Johar, Siti Fatimah Noor Mat (2017)
Introduction The goal of this study is to identify early and late burn complications among major burn patients. This study also evaluated the effect of total body surface area (TBSA) of burn towards posttraumatic stress disorder (PTSD) and depression. Association between TBSA and quality of life (QoL) was also identified. Methods This study was a cross-sectional study involving adult major burn patients from 2006 until 2016. Validated psychometric questionnaires that were used to screen for PTSD and depression in post major burn patients are, Malay PTSD Checklist for Civilians (MPCL-C), Trauma Symptom Inventory-2 (TSITM-2), Beck Depression Inventory- Malay (BDI-Malay) and Center for Epidemiological Study – Depression scale (CES-D). A Malay translated Burn Specific Health Scale – B was used to evaluate post major burn QoL. The difference of mean TBSA and PTSD as well as TBSA and depression were addressed using Independent t-test. The association between TBSA and QoL was addressed using simple linear regression. Results A total number of 55 patients voluntarily participated in answering the psychometric battery. Early complications that were identified among the major burn patients were acute stress disorder (0.72%), renal failure (0.72%), heart failure (1.08%), respiratory failure and infection (1.44%), Systemic Inflammatory Response Syndrome (2.16%), sepsis (2.52%) and infected wound (2.88%). Late complications that were identified include, corneal defect (0.36%), alopecia (0.72%), keloid (0.72%), ear deformity (1.08%), contracture (5.04%) and hypertrophic scar (10.1%). Results based on the MPCL-C and TSI-2, indicated that there were no significant difference of mean TBSAbetween patients who has PTSD and no PTSD, MPCL-C, p > 0.05 and TSI-2, p > 0.05. However, when the results of BDI and CES-D were compared, there were significant difference of mean TBSA between patient who has depression and those who dont have depression. Based on BDI, for patients with depression; the average mean TBSA is 17.1%, p < 0.05. Based on CES-D, for patients with depression; the average mean TBSA is 14.7%, p < 0.05. There is a significant association between major burns TBSA and QoL with p<0.05. Based on the model summary output, the variable TBSA explains 37.2% of the variability in QoL. This indicates, the higher level of TBSA leads to poor quality of life. For TBSA more than 25% it was reported that the QoL was 45.67 lesser when compared with TBSA less than 15%. Conclusion This study identified early and late burn complications among major burn patient through a burn database and burn proforma from 2006 until 2016. This study has found significant effect of TBSA towards depression, while no significant effect towards PTSD. Findings provide some evidence for poor QoL post major burn in a negative direction. It is suggested all major burn patients be screened for PTSD and depression as original sample size was small and it carries a significant impact towards patient’s well being beyond physical recovery from burn. All major burn patients’ quality of life should be evaluated as well, as it reflects the final outcome of healing holistically.